Identification of M2 tidal velocity and energy in the eastern waters of Aceh based on numerical simulation. Issue 1 (February 2021) - Didta, P S; Ikhwan, M; Haditiar, Y; Wafdan, R; Muhammad, M; Ramli, M; Muchlisin, Z A; Rizal, S
Abstract: The influence of the M2 harmonic component in the waters of East Aceh is more significant than the other components. It is due to the fluctuation in M2 amplitude, which affects the tides. This study aims to compare the model currents velocity simulation results with data from the Geospatial Information Agency and TPXO7.2 and find the tidal energy extraction value of M2. The modeling method used is the non-hydrostatic method. The research location is in Aceh's eastern waters by taking two research stations, namely Lhokseumawe waters and Langsa waters. The resulting tidal flow velocity in Lhokseumawe waters is 0.8344 m/s, while in Langsa waters, it is 0.8485 m/s. The tidal current strength in Lhokseumawe Waters is 1.2223 x 104 kW and Langsa Waters 1.2854 x 104 kW. Based on these results, Langsa waters have a tidal current speed higher than Lhokseumawe waters, which is 0.0241 m/s, with a tidal current strength of 6.31 x 102 kW. Due to differences in the depth layer or friction movement of the bottom of the waters and the characteristics of Lhokseumawe waters, which are wider than Langsa waters.